Risk factors associated with preterm labor in young mothers assisted in a hospital of Peru - Rocio Huarcaya-Gutierrez; Mayra Cerda-Sanchez; John Barja-Ore (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: Preterm labor is one of the main causes of neonatal morbidity and mortality whose origin is associated with the presence and interaction of factors related to the mother and her environment.  Objective: To determine the risk factors associated with preterm labor in young mothers assisted in a Hospital of Lima, Peru.  Methods:  A non experimental, analytic and retrospective study of 32 mothers with preterm labor and 292 with term delivery (selected at random), was carried out from January to August, 2016 in the hospital center above mentioned. The chi-square test of Fisher test was used, as it was necessary, as well as the odds ratio (OR) with its confidence intervals of 95 %.  Results: The social demographic factors as instruction, occupation and marital status were not related to preterm labor; as long as, antenatal factors (body mass index and history of preterm labor) were significantly associated and clinical factors (urinary tract infection, early rupture of membranes and preeclampsia) demonstrated a statistical association.  Conclusions: The antenatal body mass index ≥25 kg/m2, history of preterm labor, urinary infection, early rupture of membranes and preeclampsia, significantly increased the risk of preterm labor.